Fractionating of Calcium in Tuber and Leaf Tissues Explains the Calcium Deficiency Symptoms in Potato Plant Overexpressing CAX1 - Gao, Hongbo; Wu, Xiaolei; Zorrilla, Cinthya; Vega, Sandra E.; Palta, Jiwan P. (Frontiers in Plant Science, 2020)
Consistent with reports on other plants we recently reported that a potato transgenic line (AT010901) overexpressing sCAX1show classic symptoms of calcium deficiency shoot tip injury, leaf curling, leaf margin necrosis and tuber interal defects such as hollow heart and brown spots.The present study was undertaken to quantify calcium in various fraction of leaf and tuber tissues of this transgenic and wild type potato clones to understand the development of these deficiency symptoms at normal calcium nutrition (1mM) and its mitigation at higher calcium nutrition (10mM). Plants were grown in controlled environment growth chamber and watered with balanced nutrient solution containing either 1 or 10 mM calcium.The plants overexpressing sCAX1 showed calcium deficiency symptoms while sequestering calcium in the vacuole as calcium oxalate crystals. Various fractions of calcium were quatified in the youg and mature leaves as well as tuber tissue. A reduced concentration of water soluble fraction of calcium was most important factor related to the development of calcium deficiency symptoms in the line overexpressing sCAX1. Furthermore, an increase in this fraction appear to explain the alleviation of the deficiency symptoms in these transgenic plants.Ours is the first study to document the significance of water-soluble calcium in the development of calcium-deficiency symptoms in the potato transgenic lines overexpressing sCAX1. Furthermore, our result demonstrates that an increase in this fraction plays a significant role in the alleviation of calcium deficiency symptoms when calcium concentration in the nutrient media is increased. These results provide important insight on the role of sCAX1 in the calcium homeostasis.